Genetic Variations Affect Chemotherapy Outcomes: A Role of the Spindle-assembly Checkpoint - Sinjini Sarkar; Ranita Pal; Trisha Choudhury; Manisha Vernekar; Partha Nath; Vilas D. Nasare (Indian Journal of Public Health)
Cancer patients suffer from complicated chemotoxicity. Pharmacogenomics can help stratify patients by predicting their response to treatment and susceptibility toward severe side effects. The spindle-assembly checkpoint (SAC) is an important pathway that is activated by platinum and taxane compounds and plays a crucial role in their cytotoxic activity. This study investigated a SAC component, Budding Uninhibited by Benzimidazoles 3 (BUB3), its expression, and genetic variants in advanced ovarian cancer patients treated with paclitaxel–carboplatin chemotherapy. Among 80 patients, BUB3 expression correlated with chemosensitivity, suggesting its potential as a predictive marker for chemotherapy response. However, high BUB3 expression was associated with a higher risk of poor survival. In addition, genetic polymorphisms in BUB3 (rs11248416 and rs11248419) were significantly linked to chemotherapy-related toxicities, with rs11248416 showing a negative impact on the patient’s physical quality of life.